Objective Monitoring of Spectacle Wearing Times in Adult Subjects Using the Theramon® Thermosensor - Abaza A (Dove Medical Press, 2021)
Annegret Abaza,1 Gideon Wahl,1 Constanze Kortüm,1 Kai Januschowski,1,2 Dorothea Besch,1 Charlotte Schramm1 1Department of Ophthalmology, Eberhard-Karls-University, Tuebingen, Germany; 2Department of Ophthalmology, Eye Clinic Sulzbach, Sulzbach, Saar, GermanyCorrespondence: Annegret AbazaDepartment of Ophthalmology, Eberhard-Karls-University, Elfriede-Aulhorn-Str. 7, Tuebingen, 72076, GermanyTel +49 7071-2988088Fax +49 7071-293749Email annegret.abaza@med.uni-tuebingen.dePurpose: To find a reliable method to determine the wearing times of glasses in adults objectively on the basis of temperature measurements of the small-sized theramon® thermosensor device (TM) from orthodontics. Furthermore, the reliability of the determined wearing times during well and poor position of spectacles was explored. To address the previously reported lack of accuracy during higher outside temperatures, this study was conducted in midsummer and autumn.Patients and Methods: Twenty adults wore their spectacles with three TMs attached to both inner sides and the right outer side in a period of three consecutive days. They were asked to report wearing and non-wearing times, indoor and outdoor activities and subjective perception of spectacle position as accurately as possible. To find the most reliable way to determine spectacle wearing times compared to protocolled wearing times, we applied and evaluated temperature categorizing methods and visual analysis of time logged temperatures. Percent error and percent accuracy of each method were calculated. The methods mentioned were applied and evaluated to determine poor spectacle position.Results: Median percent errors of the most reliable determination methods were < 10% with an accuracy between 90% and 96%. Comparing the most reliable methods, determinations on the basis of midsummer measurements (median percent error 0% to 2%, median percent accuracy 96%) were more accurate than on the basis of autumn measurements (median percent error − 5% to − 20%, median percent accuracy 90%). Poor spectacle position could be determined with a median percent error of 0% and a median percent accuracy of 100% by analysing the temperature measurements of TM’s visually.Conclusion: A reliable and objective determination of spectacle wearing times is possible on the basis of TM temperature measurements in a standard clinical setting. Measurements of one inner TM seem to be sufficient to determine the wearing times and are more appealing. Poor spectacle position can be determined reliably by analysing visually the time logged temperatures. The findings of this study require further studies on larger groups of affected, amblyopic patients and children, to analyse the real impact of spectacle wearing times and poor spectacle position on visual development.Keywords: amblyopia, spectacle wearing times, objective monitoring, theramon® thermosensor, spectacle adherence